Preparation of Laundry Soap from Palm Oil and Lye from Ash of Dry Eucalyptus Tree. - Bwambale, Gerald (Kabale University, 2025)
Alkaline was extracted using a conventional process utilizing the ash from eucalyptus trees. Using a conventional process, the alkaline extract was used to make soap. A physicochemical test was performed on the final soap. White in color, rough and hard in texture, and with a saponification value of 171 mg/KOH/g. This suggests that the soap's white color results from bleaching the oil sample, and that the soap's hardness is caused by a high concentration of K+ ions in the manufactured soap, as evidenced by the emulsification test results (observed), foam test results (form lightly with moderate persistence), and foam height measurements (1.1 cm). Reactions with salts NaCl, KCl, and NH4Cl (form white ppt) but soluble in water, Ca2+, Fe2+, Mg 2+ form (white gelatinous ppt) and form an insoluble complex with water. The reaction of soap with 1 drop of phenolphthalein gave (pink color) and the reaction of the soap with 3 M HCl gave (a colorless solution) to ascertain the quality of soap produced. These properties tested showed that the soap prepared using the traditional method gave soap that could be compared with any other soap. Upon comparing with white star soap by Mukwano company similar properties were observed in the emulsification test, reaction with metals, reaction with acids, and test for alkalinity or acidity. However, some differences occurred in PH (white star soap PH 10.4 and prepared soap PH 9.1), foam test (white star soap; foam has longer persistence and prepared soap has average persistence), foam height (white star soap; 1.7 cm and prepared soap 1.1 cm).